Apparent Feminism as a Methodology for Technical Communication and Rhetoric. (January 2016) - Frost, Erin A.
This article introduces apparent feminism, which is a new approach urgently required by modern technical rhetorics. Apparent feminism provides a new kind of response that addresses current political trends that render misogyny unapparent, the ubiquity of uncritically negative responses to the term feminism, and a decline in centralized feminist work in technical communication. More specifically, it suggests that the manifestation of these trends in technical spheres requires intervention into notions of objectivity and the regimes of truth they support. Apparent feminism is a methodology that seeks to recognize and make apparent the urgent and sometimes hidden exigencies for feminist critique of contemporary politics and technical rhetorics. It encourages a response to social justice exigencies, invites participation from allies who do not explicitly identify as feminist but do work that complements feminist goals, and makes apparent the ways in which efficient work actually depends on the existence and input of diverse audiences.